Depressive mood and children: Europe and South Korea - Antonio Rodríguez Andrés; Rosemary L. Hopcroft; Yong-hwan Noh (Institute for Advanced Development Studies (INESAD), 2011)
Using data for the third wave from the European Social Survey (ESS) and the Fourth Korean National Health and Nutrition Examination Survey (K-NHANES), this research examines the relationship between having children at home and depression among men and women aged 18-75 years. Multilevel and probit regression models are applied. Our results show that there is a gender differential in depression. Having children at home improves psychological well-being for men only in 23 European countries and South Korea. In Europe we also find that depression tends to be lower in countries in which per capita income is higher. The results also show that household income is negatively associated with levels of depression in South Korea.
Keywords: I12; O57; Z13; J13; 330; Depression; Europe; Cross-national analysis; Children; Multilevel model; Probit model